STRUCTURAL AND SEMANTIC FEATURES OF ANTONYMS IN ENGLISH AND UZBEK LANGUAGES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article examines the structural and semantic characteristics of antonyms in the English and Uzbek languages. Antonyms play a crucial role in lexical semantics because they express contrast and opposition between meanings. The study analyzes structural types of antonyms such as root antonyms, affixal antonyms, and compound antonyms, as well as their semantic classification including gradable, complementary, and conversive antonyms. The article also compares similarities and differences between English and Uzbek antonym systems. The research demonstrates that although these languages belong to different language families, they share universal semantic patterns while exhibiting distinct structural features due to their linguistic typology.